(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
The traumatic experiences of street children develop from neglect and physical abuse along with witnessing violent situations, which heavily damages both their mental health and family bonds. Learning about trauma effects on these bonding relationships becomes necessary for building effective support and reintegration programs. The research evaluates traumatic experiences’ influence on Lusaka Street children’s family bonds while studying factors which promote and hinder their reintegrative success. The study relied on qualitative methods through extensive one-on-one interviews with both street children and their families to research the distressing behavioural responses created by trauma. The research outcomes show that traumatic experiences create substantial obstacles to family reintegration because they promote emotional separation and distrust as well as destructive behaviours that include anger control issues and drug use. The combination of resilience in children, sustained family backing, and community support generated better outcomes concerning reintegration. The research evidence shows that street children need trauma-based interventions alongside family therapeutic alignment and dependable community support systems to rebuild trust between children and their families through emotional reconnection, thus improving reintegration efforts.